Kontroversi Nasikh Mansukh Dalam Alquran - Agus Handoko (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The discipline of Nasikh wa Mansukh is an essential component of the knowledge of the Quran that the mufassir must possess in order to interpret the verses of the Quran. Nasakh is the abolition of syara' law by the proposition of syara' that descends in time, then when between the two there are messages that appear contradictory at first glimpse and cannot be compromised. This manuscript theory is used as an alternative methodology to resolve apparent contradictions (ta'arudh) between verses of the Qur'an that cannot be resolved using existing methodologies such as takhsih al-'amm, taqyd al-muthlaq, and others. Naskh only appears in shari'a law such as Amr (command) and Nahyi (prohibition), both shorih (clearly) in orders or with words khabar (news) that contain the meaning of orders and prohibitions, provided that they are not related to matters of faith such as Allah's essence and nature, the books, and the last day. In addition to referencing moral ethics and the fundamentals of worship and mu'amalah. Thus, the discussion of nasikh mansukh in the Qur'an cannot be separated from the capacity of a mufassir or mujtahid to investigate God's messages, both in the field of shari'a law and ethics, which are perennially valid.Keywords: Nasikh; Mansukh; Al-Qur'an Abstrak:Disiplin Nasikh wa Mansukh merupakan komponen penting dari pengetahuan Al-Qur'an yang harus dimiliki mufassir untuk menafsirkan ayat-ayat Al-Qur'an. Nasakh adalah penghapusan hukum syara' oleh dalil syara' yang turun dalam waktu, kemudian di antara keduanya terdapat pesan yang sekilas tampak kontradiktif dan tidak dapat dikompromikan. Teori manuskrip ini digunakan sebagai metodologi alternatif untuk menyelesaikan kontradiksi yang tampak (ta'arudh) antara ayat-ayat Al-Qur'an yang tidak dapat diselesaikan dengan menggunakan metodologi yang ada seperti takhsih al-'amm, taqyd al-muthlaq, dan lain-lain. Naskh hanya muncul dalam hukum syariat seperti Amr (perintah) dan Nahyi (larangan), baik shorih (jelas) dalam perintah maupun dengan kata khabar (berita) yang mengandung arti perintah dan larangan, asalkan tidak berkaitan dengan masalah iman seperti hakikat dan sifat Allah, kitab-kitab, dan hari akhir. Selain merujuk pada etika moral dan dasar-dasar ibadah dan mu'amalah. Dengan demikian, pembahasan nasikh mansukh dalam al-Qur'an tidak lepas dari kemampuan seorang mufassir atau mujtahid dalam mengkaji pesan-pesan Tuhan, baik dalam bidang hukum syariat maupun etika, yang berlaku sepanjang masa.Kata Kunci: Nasikh; Mansukh; Al-Qur'an